Monitoring Impacts of the Gulf Stream and its Rings on the Physics, Chemistry, and Biology of the Middle Atlantic Bight Shelf and Slope from CMV Oleander - Magdalena Andres; Thomas Rossby; Eric Firing; Charles Flagg; Nicholas Bates; Julia Hummon; Denis Pierro; Timothy Noyes; Matthew Enright; Jeffery O’Brien; Rebecca Hudak; Shenfu Dong; et al. (Oceanography, 2025)
Sustained observation is key to measuring physical and ecological variability in the Northwest Atlantic. Here we illustrate how a partnership with a merchant marine container vessel in service between New Jersey and Bermuda twice per week gives scientists a unique window into upper ocean currents, water properties, and marine ecology. Scientific observations collected from CMV Oleander, operated by Bermuda Container Line/Neptune Group, enable cross-disciplinary research, complement satellite measurements, and contribute to global observing programs—including the Global eXpendable BathyThermograph (XBT) Network, the Surface Ocean CO2 Atlas (SOCAT), and the Continuous Plankton Recorder (CPR) Survey. Recent co-located measurements along the Oleander Line document that fronts in temperature, salinity, and carbon dioxide concentrations align with the (sub)mesoscale circulation patterns. The sustained observations show warming and shrinking of the Slope Sea, a northward shift of the Gulf Stream, and warming of the “18°C water” (subtropical North Atlantic mode water) to 19°C.

Physical Characteristics and Evolution of a Long-Lasting Mesoscale Cyclonic Eddy in the Straits of Florida - Yingjun Zhang; Chuanmin Hu; Vassiliki H. Kourafalou; Yonggang Liu; Dennis J. McGillicuddy; Brian B. Barnes; Julia M. Hummon (Frontiers in Marine Science, 2022)
Ocean eddies along the Loop Current (LC)/Florida Current (FC) front have been studied for decades, yet studies of the entire evolution of individual eddies are rare. Here, satellite altimetry and ocean color observations, Argo profiling float records and shipborne acoustic Doppler current profiler (ADCP) measurements, together with high-resolution simulations from the global Hybrid Coordinate Ocean Model (HYCOM) are used to investigate the physical and biochemical properties, 3-dimensional (3-D) structure, and evolution of a long-lasting cyclonic eddy (CE) in the Straits of Florida (SoF) along the LC/FC front during April–August 2017. An Angular Momentum Eddy Detection Algorithm (AMEDA) is used to detect and track the CE during its evolution process. The long-lasting CE is found to form along the eastern edge of the LC on April 9th, and remained quasi-stationary for about 3 months (April 23 to July 15) off the Dry Tortugas (DT) until becoming much smaller due to its interaction with the FC and topography. This frontal eddy is named a Tortugas Eddy (TE) and is characterized with higher Chlorophyll (Chl) and lower temperature than surrounding waters, with a mean diameter of ∼100 km and a penetrating depth of ∼800 m. The mechanisms that contributed to the growth and evolution of this long-lasting TE are also explored, which reveal the significant role of oceanic internal instability.

The Global Ocean Ship-Based Hydrographic Investigations Program (GO-SHIP): A Platform for Integrated Multidisciplinary Ocean Science - Bernadette M. Sloyan; Rik Wanninkhof; Martin Kramp; Gregory C. Johnson; Lynne D. Talley; Toste Tanhua; Elaine McDonagh; Caroline Cusack; Eleanor O’Rourke; Evin McGovern; Katsuro Katsumata; Steve Diggs; et al. (Frontiers in Marine Science, 2019)

The Scientific and Societal Uses of Global Measurements of Subsurface Velocity - Zoltan B. Szuts; Amy S. Bower; Kathleen A. Donohue; James B. Girton; Julia M. Hummon; Katsuro Katsumata; Rick Lumpkin; Peter B. Ortner; Helen E. Phillips; H. Thomas Rossby; Lynn Keith Shay; Charles Sun; et al. (Frontiers in Marine Science, 2019)

Improving the Quality and Accessibility of Current Profile Measurements in the Southern Ocean - Eric Firing; Julia Hummon; Teresa Chereskin (Oceanography, 2012)